2019
DOI: 10.1039/c8ra08547a
|View full text |Cite
|
Sign up to set email alerts
|

The structural, electronic and optical properties of γ-glycine under pressure: a first principles study

Abstract: The crystallized amino acid γ-glycine is a large band gap insulator that shows promise in the fields of photonics and non-linear optics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…[34] glycine at ambient and high pressures was attempted many times. [48][49][50][51][52] Some recent papers propose the structures of some new polymorphs, but their existence has never been confirmed experimentally. [53,54] In all the glycine polymorphs there is a common structureforming motif -a head-to-tail hydrogen-bonded chain formed by the glycine zwitter-ions (Figure 4a).…”
Section: Figurementioning
confidence: 99%
“…[34] glycine at ambient and high pressures was attempted many times. [48][49][50][51][52] Some recent papers propose the structures of some new polymorphs, but their existence has never been confirmed experimentally. [53,54] In all the glycine polymorphs there is a common structureforming motif -a head-to-tail hydrogen-bonded chain formed by the glycine zwitter-ions (Figure 4a).…”
Section: Figurementioning
confidence: 99%
“…Semiconductive properties have been studied not only in piezoelectric peptides, but also in piezoelectric amino acids and proteins. The bandgap for a γ -glycine crystal was calculated as 5.02 eV, indicating insulation characteristics [111]. However, some previous studies revealed that proteins possessed inherent conductivity properties [112–114].…”
Section: Properties and Applications Of Peptide And Metabolite Matmentioning
confidence: 99%
“…Computation method. The theoretical calculation was performed using the CASTEP module of Material Studio [ 26 , 27 , 28 ]. A four-layer supercell of 2 2 2 with a vacuum layer thickness of 13 Å was used to simulate the surface of the catalyst.…”
Section: Methodsmentioning
confidence: 99%